Ecological risks in river basins: a comparative analysis of steppe and forest Ukrainian areas - Skyba, Viktoriia; Скиба, Вікторія Павлівна; Скиба, Виктория Павловна; Kopylova, O. M.; Vozniuk, N. M.; Likho, O. A.; Pryshchepa, A. M.; Budnik, Z. M.; Gromachenko, K. Y.; Turchina, К. P. (My University, 2021)
One of the most important goals of the state environmental policy of Ukraine for the period up to 2030 is to reduce the environmental risks in order to minimize their impact on ecosystems, socio-economic development, and public health. This, in turn, is possible after reducing anthropogenic load and introducing environmental risk management. The purpose of the research was to establish the peculiarities of the ecological risk formation in deteriorating river basins for different natural and climatic zones of Ukraine on the example of the rivers Styr (Western Polissya) and Molochna (Steppe zone). The river basins within different natural and climatic zones of Ukraine differ in surface runoff formation, hydrological, hydrochemical regimes, and the features of aquatic ecosystems. However, these are affected by similar anthropogenic factors, resulting in conditions for emerging risks of the river basins' ecological status deterioration. Establishing the anthropogenic load level and evaluating the ecological status of Styr and Molochna River basins that were made using the induction coefficient of the anthropogenic load (ICAN): this showed that in the basins of these rivers, there is excessive usage of the land and water resources. Moreover, there is also a probability of environmental risks emerging in these rivers' deteriorating basins related to the degradation processes development. Because of the water quality evaluation in the rivers Styr and Molochna, it was established that primarily the pollutants belonging to the trophy-saprobiological block determined the water quality in the rivers. For the Styr River, heavy metal pollution (block of toxic and radiation substances) is also inherent, but their high content is also natural. The interactive development of the World Resources Institute (WRI), using the Aqueduct geospatial database, allowed us to establish the probability of water risk in the Styr and Molochna River basins and predict the development of environmental risks and water stress. It has been established that the Molochna River basin, which is located in the Steppe zone of Ukraine, is more vulnerable to the development of environmental risks. Thus, the anthropogenic factors, under the influence of which the ecological state of river basins in the zone of Western Polissya and Steppe zones of Ukraine are formed, significantly level the natural features of these basins' processes create the conditions for ecological risks with similar consequences.
Keywords: river basin; ecological risks; anthropogenic load; ecological condition; water quality; degradation processes; water risk; water stress